2021
DOI: 10.1016/j.jbc.2021.100962
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of miR-30a by YAP impacts PTPN13 and KLF9 levels and Schwann cell proliferation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(219 reference statements)
0
6
0
Order By: Relevance
“…While the function of the YAP-TEAD complex has been extensively characterized, only a few studies have examined YAP function as a regulator of gene expression via microRNAs. [ 34 , 35 ] A recent study revealed that YAP binds to the promoter and regulates the expression of miR-30a. YAP regulation of Schwann cell proliferation and death is mediated through miR-30a regulation of protein tyrosine phosphatase non-receptor type 13 (PTPN13) in Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the function of the YAP-TEAD complex has been extensively characterized, only a few studies have examined YAP function as a regulator of gene expression via microRNAs. [ 34 , 35 ] A recent study revealed that YAP binds to the promoter and regulates the expression of miR-30a. YAP regulation of Schwann cell proliferation and death is mediated through miR-30a regulation of protein tyrosine phosphatase non-receptor type 13 (PTPN13) in Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…YAP regulation of Schwann cell proliferation and death is mediated through miR-30a regulation of protein tyrosine phosphatase non-receptor type 13 (PTPN13) in Schwann cells. [ 34 ] Hence, there are complex mutual regulation relationships between miR-30a and the YAP-TEAD complex, which require further study and clarification. These regulatory mechanisms are not limited to specific disease environments, such as sepsis-AKI, nor do they only occur in Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…In immature SCs, YAP/TAZ are found at high nuclear levels and promote vigorous proliferation [17, 31, 32]. In actively proliferating human Schwann (hSC2λ) cell model, YAP could promote proliferation through inducing the expression of miR-30a, which is a microRNA that could downregulate the growth-suppressive protein PTPN13 [18]. In YapTaz dKO immature SCs, genes related to cell growth such as Amotl2, Fgf1, Ect2 , and Ddah1 were significantly downregulated; a dramatic drop was also observed in the expression of cell cycle-associated genes Ccnj , Cdk6 , Pim3 , and Mycn [17].…”
Section: Hippo Pathway In Pns Developmentmentioning
confidence: 99%
“…Hippo pathway shows the magic of switching between promoting proliferation and facilitating myelination in neural crest cell (NCC) and SC development [15][16][17][18]. The brief introduction of the development of SCs and the role of Hippo pathway during the development will be elaborated on below.…”
Section: Hippo Pathway In Pns Developmentmentioning
confidence: 99%
“…The cell uses a variety of tactics such as RNA-binding proteins, transcription factors, and protein and RNA enzymes (e.g., exoribonucleases and endoribonucleases) to inhibit or promote each phase [5]. A recent study indicated that YAP (yes-associated protein, Hippo pathway) regulates miR-30a via TEA (transcriptional enhanced associate) domain (TEAD) transcription factors [24]. The methylation of miR-30 genes also causes their downregulation [25].…”
Section: Regulation Of Mir-30mentioning
confidence: 99%